Parameters influencing vortex growth and detachment on unsteady aerodynamic profiles. (26th May 2015) - Widmann, A.; Tropea, C.
Abstract : Experiments with a pitching and plunging airfoil are conducted in order to investigate the mechanisms responsible for the formation and detachment of leading edge vortices (LEVs). The chord length is varied from 90 to 180 mm, keeping all other non-dimensional parameters constant, specifically the Reynolds number (17 000), the Strouhal number (0.25), the reduced frequency (0.5) and the effective angle of attack history. It is shown that the mechanism of vortex detachment changes with chord length, evident in a corresponding change in flow topology. One mechanism scales with chord length, the other is attributed to viscous effects in the boundary layer. For the latter mechanism a new scaling of the LEV circulation is introduced. A second experiment investigates the influence of the reduced frequency on the LEV circulation and detachment mechanisms, again keeping all other non-dimensional parameters constant.